Educational Gardens and Climate Change Education: An Analysis of Spanish Preservice Teachers' Perceptions - Diego Corrochano; Enzo Ferrari; María Antonia López-Luengo; Vanessa Ortega-Quevedo (MDPI AG, 2022)
Educational gardens are powerful outdoor learning environments to address the subject of climate change and foster climate action. Using an online questionnaire, this study examines the influence of the main sociodemographic and academic factors, and the role of connectedness to nature, on the perception of educational gardens as contexts of climate change education (CCE) among Spanish preservice teachers (PSTs). The sample consisted of 889 PSTs enrolled in 9 university campuses of Spain. The statistical analyses performed evidenced that women are more likely to use educational gardens than men and that there is a progressive decrease in the positive perception of PSTs about the usefulness of gardens for CCE as the educational level at which they are being trained increases. Statistics also revealed that the variable connectedness to nature and the rating of the importance of educational gardens in CCE are not significantly related. Nevertheless, the Mann-Whitney U test indicated that PSTs who scored higher on connection to nature wished to broaden their knowledge of sustainable agriculture and, thus, connectedness to nature could be considered a predictor of environmental attitudes, each influencing the other. Based on these findings, recommendations for PSTs' training in the CCE context are provided.